A review of the maternal iron and folic acid supplementation programme in Nepal: Achievements and challenges - Naveen Paudyal; Kedar Raj Parajuli; Vanessa Garcia Larsen; Ramesh Kant Adhikari; Madhu Dixit Devkota; Sanjay Rijal; Stanley Chitekwe; Harriet Torlesse (Wiley, 2022)
Abstract In the late 1990s, an estimated 75% of pregnant women in Nepal were anaemic. Although iron and folic acid (IFA) supplements were available free of charge, coverage among pregnant women was very low. In response, the Government of Nepal launched the Iron Intensification Programme (IIP) in 2003 to improve the coverage of IFA supplementation and anthelminthic treatment during pregnancy, as well as promote the utilization of antenatal care. This review examined how the IIP programme contributed to Nepal's success in increasing the consumption of IFA supplements during pregnancy. Nepal's cadre of Female Community Health Volunteers were engaged in the IIP to support the community‐based distribution of IFA supplements to pregnant women and complement IFA distribution through health facilities and outreach services. As a result, the country achieved a fourfold increase in the proportion of women who took IFA supplements during pregnancy between 2001 and 2016 (from 23% to 91%) and a 12‐fold increase in the proportion who took IFA supplements for at least 90 days during pregnancy (from 6% to 71%). The increase in coverage of IFA supplements accompanied an increase in the coverage of antenatal care during the same period. By 2016, the prevalence of anaemia in pregnant women decreased to 46%, highlighting the need to tackle other causes of anaemia and improve haemoglobin concentration before pregnancy, while maintaining the successful efforts to reach pregnant women with IFA supplements at the community level.